Vibration reliability characterization and damping capability of annular periodic metal rubber in the non-molding direction. (1st October 2019) - Yang, Pei; Bai, Hongbai; Xue, Xin; Xiao, Kun; Zhao, Xu
Highlights: The novel dynamic testing system is developed and the parameter identification. The optimal 180° large angle crisscross by entangled wire mesh is determined. Two fabrication technologies are introduced associated with vibration capability. Vibration reliability characterization of annular periodic metal rubber is studied. Abstract: This paper aims to investigate the vibration reliability characterization and damping performance of annular periodic metal rubber subjected to cyclic dynamic loading. A typical annular or ring-shaped metal rubber benchmark, which leads to a particularly pronounced looseness or damage characteristics along the non-molding direction after cyclic dynamic loading, was introduced. For the fabrication of the studied metal rubber, entangled wire mesh and woven wire mesh were adopted to analyze and optimize the micro-structure associated with the vibration damping capability. The experimental dynamic testing system was developed as well as the corresponding parameter identification. The geometric coefficient in terms of cross-section distortion was proposed to assess the vibration reliability after cyclic dynamic loading. The effects of density and wire diameter on the damping performance of annular metal rubber in the non-molding direction were examined and analyzed in detailed. The results indicate that the 180° large angle crisscross by entangled wire mesh is a relatively optimal fabrication solution for the studied benchmark. The interrelationship of wire diameter and density on key damping capabilities such as energy dissipation, dynamic average stiffness and loss factor should be evident. Some preliminary results of the optimal process parameters are obtained and provide an alternative method for the design of periodic metal rubber damper in terms of individual application.